Review paperIncreased vesicular and vacuolar transendothelial transport in traumatic human brain oedema. A review - Castejón, Orlando J. (Folia Neuropathologica, 2013)
The endothelial vacuolar and vesicular transports in traumatic human brain oedema have been reviewed and compared with experimental brain oedema in order to establish their role in both oedema formation and oedema resolution. Normal or “non-activated” and “activated” capillaries are found. The activated capillaries showed predominantly an enhanced abluminally orientated vesicular transport by means of small, medium and large uncoated and clathrin coated vesicles, as well as the presence of endothelial tubular structures. Activation of the endothelial nuclear zone is featured by the increased amount of micropinocytotic vesicles. Vesicles internalizing to the hypertrophic Golgi complex, lysosomes and multivesicular bodies are observed. The protein vacuolar transport is predominant in most cortical capillaries. A wide spectrum of endothelial cell mechanisms is observed increasing the vesicular and vacuolar transport, such as deep invaginations of the luminal surface, large coated vesicles, tubular structures, and transient and incomplete transendothelial channels formed either by chained plasmalemmal vesicles or elongated protein-containing vacuoles. Uncoated vesicles are seen surrounding lysosomes. Vesicular transport might be discriminated between abluminally orientated or transendothelial transport (oedema formation) and intraendothelial transport (oedema resolution) directed towards cell lysosomes to be degraded by lysosomal enzymes. The transendothelial passage via large vacuoles is mainly caused by macromolecular protein transport.